The Islamist movement in Morocco: Main actors and regime responses - Julie E. Pruzan-Jørgensen (Danish Institute for International Studies (DIIS), 2010)
Morocco's formally accepted Islamist party, the Justice and Development Party (PJD), has further underlined its recognition of the authoritarian regime in response to a disappointing electoral showing and tough competition from the new Authenticity and Modernity Party (PAM). In contrast, the forbidden, although tolerated, Justice and Spirituality Movement (Al Adl wal Ihsan) retains its principled oppositional role. While there is speculation that this may change when its ailing and aging leader and founder, Sheikh Yassine, passes away, it seems most likely that Justice and Spirituality will retain its role as the main oppositional movement in Morocco in the near future.
Keywords: 300; Islam; Politische Partei; Politische Opposition; Marokko